The Intersection of Social Engineering and Rehabilitation Law: Evaluating the Effectiveness of Law Reform for Drug Addicts in Indonesia - Siti Ngaisah; Wredha Danang Widoyoko; Haryono Haryono; Diah Ayu Rahmawati; Ruchan Sanusi (Westscience Press, 2024)
This study examines the intersection of social engineering and rehabilitation law in Indonesia, focusing on the effectiveness of legislative reforms addressing drug addiction. By employing a juridical analysis of legislation, the research evaluates the alignment of Indonesia’s Narcotics Law with social engineering principles aimed at shifting societal perceptions of addiction from punitive to rehabilitative. Findings reveal significant challenges, including limited institutional capacity, societal stigma, and inconsistencies in law enforcement, which undermine the intended outcomes of rehabilitation laws. Comparative insights from global best practices underscore the need for integrated and well-resourced strategies to enhance the effectiveness of rehabilitation-focused legal frameworks. Recommendations are proposed to address these challenges through legislative revisions, institutional strengthening, and public awareness campaigns.